Does cataract surgery reduce the long‐term risk of glaucoma in eyes with pseudoexfoliation syndrome?. (9th January 2016) - Kristianslund, Olav; Østern, Atle E.; Råen, Marianne; Sandvik, Gunhild F.; Drolsum, Liv
Abstract: Purpose: To compare glaucoma development and intraocular pressure (IOP) in the longer term following phacoemulsification cataract surgery in eyes with and without pseudoexfoliation syndrome (PEX). Methods: Fifty‐one patients with PEX were compared with 102 age‐ and gender‐matched controls without PEX. Patients were re‐examined a mean of 76 (SD 5.4) months after cataract surgery, recording IOP, glaucoma diagnosis, glaucoma treatment and LogMAR. Data from the preoperative visit (baseline) and IOP on the first postoperative day were obtained from medical records. A glaucoma parameter was predefined as patients developing glaucoma or needing increased glaucoma treatment during the postoperative time period. Results: One new glaucoma case in each group was diagnosed postoperatively, yielding glaucoma incidences of 0.47 cases per 100 person‐years [95% confidence interval (CI) 0.006–2.61] and 0.17 cases per 100 person‐years (CI 0.002–0.95) in the PEX and control groups respectively (p = 0.53). IOP declined by 2.6 (SD 4.0) mmHg in the PEX group (p < 0.001) and 1.9 (SD 3.5) mmHg in the control group (p < 0.001) from baseline to the re‐examination, with a non‐significant group difference (p = 0.310). IOP spike (≥6 mmHg increase) was significantly associated with the glaucoma parameter, both within the PEX (p = 0.034) and the control group (p = 0.044). Conclusion: The number of newly diagnosed glaucoma cases was lower than expected 6–7 years following cataract extraction, especially in the PEX group, which indicates that PEX eyes benefit particularly from cataract surgery in terms of IOP and glaucoma development.